Factors influencing compressive strength in Batu Caves and Ipoh limestones - 447506 Noor Rohaellizza Hademi (Skudai : Universiti Teknologi Malaysia, 2005)
Project Paper (Bachelor of Petroleum Engineering) - Universiti Teknologi Malaysia, 2005